2014
DOI: 10.1007/s12257-014-0320-1
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of bioethanol production from glucose/xylose mixtures during fed-batch fermentation of co-culture and mono-culture systems

Abstract: This study presents a detailed in silico analysis of bioethanol production from glucose/xylose mixtures of various compositions by fed-batch co-culture and monoculture fermentation of specialized microbes. The monoculture consists of recombinant Saccharomyces cerevisise that can metabolize both hexose and pentose sugars while the co-culture system consists of substrate-selective microbes. Dynamic flux balance models based on available genomescale reconstructions of the microorganisms have been used to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…By using the genome-scale metabolic network of S. cerevisiae ( i FF708), Bro et al [ 12 ] reported ten genetic engineering strategies for enhancing ethanol yield at the expense of reduced glycerol production. Recently, Lisha and Sarkar [ 13 , 14 ] analysed the impact of ten genetic engineering strategies reported by Bro et al [ 12 ] on S. cerevisiae for their efficiency in enhancing the ethanol productivity in the context of batch/fed-batch coculture and monoculture fermentation. Simulations were carried out with various glucose/xylose mixtures and, for the 50/50 glucose/xylose (%/%) mixture, the batch coculture fermentation using genetically modified S. cerevisiae (consumes only glucose) and engineered E. coli strain ZSC113 (consumes only xylose) enhanced the ethanol productivity by 40.7% compared to the monoculture ( S. cerevisiae strain RWB218) fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…By using the genome-scale metabolic network of S. cerevisiae ( i FF708), Bro et al [ 12 ] reported ten genetic engineering strategies for enhancing ethanol yield at the expense of reduced glycerol production. Recently, Lisha and Sarkar [ 13 , 14 ] analysed the impact of ten genetic engineering strategies reported by Bro et al [ 12 ] on S. cerevisiae for their efficiency in enhancing the ethanol productivity in the context of batch/fed-batch coculture and monoculture fermentation. Simulations were carried out with various glucose/xylose mixtures and, for the 50/50 glucose/xylose (%/%) mixture, the batch coculture fermentation using genetically modified S. cerevisiae (consumes only glucose) and engineered E. coli strain ZSC113 (consumes only xylose) enhanced the ethanol productivity by 40.7% compared to the monoculture ( S. cerevisiae strain RWB218) fermentation.…”
Section: Introductionmentioning
confidence: 99%